Canopy cover and invasive grasses effects in distinct ecological restoration technologies: 5-y monitoring in a Brazilian subtropical forest - Dionatan Gerber; Tatiene Yumi Kiwara; Patricia Ramos de Souza; Marcos Lubke; Edgar de Souza Vismara; Fernando Campanhã Bechara (Acta Biológica Catarinense, 2017)
The establishment of canopy and the following elimination of invasive exotic grasses are among the main barriers towards the restoration of subtropical forests. We compared canopy initial cover and biological invasion by exotic grasses in different restoration technologies, up to 5-y, in Paraná State, southern Brazil. We tested three treatments in four randomized blocks as follows: T1 – passive restoration; T2 – nucleation; and T3 – high diversity plantation. We sampled 117 points per plot (54 x 40 m). We registered the presence or absence of invasive grasses cover and canopy cover percentage (using a spherical crown densiometer). The high density of fast-growing trees plus dense crowns was probably responsible for the highest shadowing and faster elimination of grasses in the plantation, while nucleation and the passive restoration showed the lowest canopy cover followed by the highest invasion by grasses. We recommend managers to use plantations to make a fast covering, although with higher inputs, or use nucleation in a long-term shadowing basis project.